2015
DOI: 10.1111/tmi.12482
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of common respiratory viruses and no evidence of Middle East Respiratory Syndrome Coronavirus in Hajj pilgrims returning to Ghana, 2013

Abstract: Abstractobjective The Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in 2012 on the Arabian Peninsula and has caused severe respiratory disease with more than 800 laboratoryconfirmed cases. The return of infected pilgrims to their home countries with a putative spread of MERS-CoV necessitates further surveillance. conclusions The prevalence of viral respiratory infections among Hajj pilgrims in both symptomatic and asymptomatic subjects was high. Although it is reassuring that MERS-CoV was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
62
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 28 publications
9
62
3
Order By: Relevance
“…The high prevalence of ILI during pilgrimage and confirmed influenza virus on the pilgrims' return to Egypt suggests a continued need for influenza prevention strategies for Egyptian Hajj pilgrims. These findings are higher than those of prior surveys where influenza virus positivity was 1.3%‐7.8% among returning Hajj pilgrims regardless of clinical status . Differences between our results and those of other studies might be due to subtle differences in sociodemographic characteristics including age distribution and prior vaccination among those surveyed.…”
Section: Discussioncontrasting
confidence: 95%
“…The high prevalence of ILI during pilgrimage and confirmed influenza virus on the pilgrims' return to Egypt suggests a continued need for influenza prevention strategies for Egyptian Hajj pilgrims. These findings are higher than those of prior surveys where influenza virus positivity was 1.3%‐7.8% among returning Hajj pilgrims regardless of clinical status . Differences between our results and those of other studies might be due to subtle differences in sociodemographic characteristics including age distribution and prior vaccination among those surveyed.…”
Section: Discussioncontrasting
confidence: 95%
“…Specifically, the several studies from Saudi Arabia, China, France, Egypt, India, Jordan, Ghana, Iran, and the UK have reported higher prevalence of flu (1.3%‐20.7%) among pilgrims compared with other viruses with flu A being more common (0.6%‐13.9%) than flu B (0.8%‐6.8%) . They also showed high rates of hAdvs (0.8%‐23.7%), hRVs (5.9%‐16.8%), non‐MERS hCoVs (0.4%‐12.8%), hPIVs (0.8%‐7.4%), hRSVs (0.2%‐7.4%), and EVs (2.0%) . In contrast, our current study showed flu A as the most predominant virus among symptomatic pilgrims in 2014 Hajj (27.8%) followed by non‐MERS hCoVs (25.7%), hRVs (16.5%), flu B (13.4%), EVs (5.2%), hAdvs (5.1%), hRSVs (4.1%), and hPIVs (2.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Barasheed et al cite two more studies on surveillance of MERS-CoV in returning Hajj pilgrims, both of which were published after the submission of our manuscript, thus highlighting the interest of MERS-CoV surveillance of Hajj pilgrims that is obviously perceived in the scientific community at the moment [1][2][3][4].…”
mentioning
confidence: 83%